Preventing the introduction of meticillin-resistant Staphylococcus aureus into hospitals. Issue 4 (December 2014) - Larsen, Jesper; David, Michael Z.; Vos, Margreet C.; Coombs, Geoffrey W.; Grundmann, Hajo; Harbarth, Stephan; Voss, Andreas; Skov, Robert L.
Highlights: We compare interventions to prevent introduction of MRSA into hospitals. Interventions vary between countries and even between hospitals. Emergence of new MRSA reservoirs poses a threat to existing interventions. Surveillance is needed to define local MRSA reservoirs. More research is needed to reduce spread from local MRSA reservoirs into hospitals. Abstract: The objective of this review was to provide an up-to-date account of the interventions used to prevent the introduction of meticillin-resistant Staphylococcus aureus (MRSA) from the expanding community and livestock reservoirs into hospitals in the USA, Denmark, The Netherlands and Western Australia. A review of existing literature and local guidelines for the management of MRSA in hospitals was performed. In Denmark, The Netherlands and Western Australia, where the prevalence of MRSA is relatively low, targeted admission screening and isolation of predefined high-risk populations have been used for several decades to successfully control MRSA in the hospital. Furthermore, in Denmark and The Netherlands, all identified MRSA carriers undergo routine decolonisation, whereas only carriers of particularly transmissible or virulent MRSA clones are subjected to decolonisation in Western Australia. In the USA, which continues to be a high-prevalence MRSA country, policies vary by state and even by hospital, and whilst guidelines from professional organisations provide a framework for infection control practices, these guidelines lack the authority of a legislative mandate. In conclusion, the changing epidemiology of MRSA, exemplified by the recent emergence of MRSA in the community and in food animals, makes it increasingly difficult to accurately identify specific high-risk groups to screen for MRSA carriage. Understanding the changing epidemiology of MRSA in a local as well as global context is fundamental to prevent the introduction of MRSA into hospitals.